Edukasi Konsep dan Penerapan Pajak Karbon bagi Mahasiswa - Irawan, Ferry; Wijaya, Suparna; Firmansyah, Amrie (Pengmasku, 2023)
Climate change caused by carbon emissions has been felt in almost all countries, including Indonesia. The government has issued policy Law Number 7 of 2021 concerning Harmonization of Tax Regulations (UU HPP) which regulates the imposition of carbon tax. Apart from that, the Government has also issued Presidential Regulation Number 98 of 2021 concerning the Implementation of Carbon Economic Value. The aim of this regulation is to reduce carbon emissions in Indonesia by imposing taxes. Community service activities are carried out through seminars aimed at providing the public with an understanding of the concept and application of carbon tax as well as elaboration of practices carried out in other countries. The material presented in this seminar includes: the concept of carbon tax, the practice of imposing carbon tax in other countries, existing regulations in Indonesia, discussion and delivery of conclusions. The implementation of the seminar consists of three stages. First, presentation of material from the resource person. Second, question and answer session with participants. The number of seminar participants was around 100 people from academics, both students and lecturers from UPN Veteran Jakarta and other universities.